Student’s communication privacy management on Facebook - Yayu Sriwartini (Jurnal Komunikasi Profesional, 2022)
The purpose of this study was to describe the management of communication privacy of Facebook users . The research used the Theory of Communication Privacy Management from Santro Petronio. The research approach was quantitative with a survey method. Data collection was carried out using questionnaires distributed online via google.doc to around 304 samples of Students of Universitas National who were active users of Facebook. The datas were presented in a frequency distribution table and analyzed by descriptive statistics. The result shows (1) most respondents were selective in publishing their personal data on Facebook. Only date of birth and religion were considered non- privacy; (2) In conveying certain information or messages through various features on Facebook, most of the respondents applied collective limitation, but still controlled the boundaries. It meant allowing others to view or read various posts, but limiting the active activities of others on their timeline; (3) Overall, the results of the study indicate that there were a communication privacy management activity of respondents on their facebook.